ANALISIS FRAUD DIAMOND TERHADAP RESTATEMENT - Wielungga Arjapratama (2020)
This research is a quantitative study that aims to determines the effect of factors in diamond theory on the possibility of scandal management. Diamond fraud theory is measured by pressure (financial target), opportunity (ineffective monitoring), rationalization (change in auditor), and competence (change in director). Scandal Management is measured by restatement. The method used is purposive sampling. The sample consisted of 106 companies listed on the Indonesia Stock Exchange in 2017 - 2018. Data were analyzed used descriptive statistical analysis and logistic regression with some help of programming data using STATA 13th. The results showed that the ineffective monitoring affected the scandal management, while the financial target, change in auditor and change of director have no effect of the scandal management.